Executive function in children with externalizing and comorbid internalizing behavior problems. (15th May 2015) - Woltering, Steven; Lishak, Victoria; Hodgson, Nick; Granic, Isabela; Zelazo, Philip David
Abstract : Background: The goal of this study is to investigate differences in executive function (EF) in children with different levels of disruptive behavior problems (DBP). Methods: Ninety‐three children between 7 and 12 years old with DBP were compared to 63 normally developing peers on a battery of EF tasks that varied in the amount of required emotion regulation ('hot' EF). Results: Differences in EF were found between DBP and comparison groups as indexed by hot EF tasks. Self‐reported emotion scales, in conjunction with physiological recordings of heart rate, confirmed that emotions were elicited during hot EF. Conclusions: Results suggest that difficulties in hot EF underlie externalizing problem behaviors in middle childhood.